حجية السنة الرتكية وآاثرها ف فتاوى جملس الرتجيح احملمدية و فتاوى جملس العلماء األندونيسي - Rudi Katamso; Reza Hilmy Luayyin (JSE: Jurnal Sharia Economica, 2022)
Sharia law is based on the Alquran and the sunna of the prophet Muhammad Shallahualahiwasallam in the first place and the basic knowledge of the sharia, by which they learn about sharia law. One of the most important things that society should be aware of, and one of the means of finding out about the sect is the Sunnah Tarkiyah, is the subject that has been decided by some fundamentalists, some of whom do not, because what was left by the prophet Shallahualahiwasallam is not called into question and is annulled. The aim of this research is to find out whether the Sunnah Tarkiyah is considered to be in the making of judgments and to compare the protest of the mohammadiyah swing council and the Indonesian ulema council with the Sunnah Tarkiyah. This type of research is a qualitative desk research in which the researcher gathers information from relevant sources and sources from the tiers council and scholars council books, and analyses it in order to obtain fatwas in protest of the Sunnah Tarkiyah, together with extrapolation, reasoning, comparison and theories from the theories of the origins of the fiqh. The main result of this research is that the researcher found that scholars differed in the authority of the Sunnah Tarkiyah, which is likely to be regarded as the same. The tit-for-tat council has also considered it in some of its fatwas, such as the pronouncement of intent, gift the good to the deceased and shaking hands after the congregation prayer. The ulema council does not dismiss the fact that in some of its fatwas, such as: praying together with the infidel; translating prayer and wall when praying; and congratulating the infidel by the words I pray.Keyword : Sunnah Tarkiyah, Methods and fatwas of the Muhammadiyah Tarjih Council, Method and fatwa of the Indonesian Ulema Council, ushul fiqih.